Community-Acquired Cavitary Pseudomonas Pneumonia Linked to Use of a Home Humidifier - Eric Woods; Gabriel Cohen; Eric Bressman; David Lin; Nathalie E. Zeitouni; Colleen Beckford; Camille Hamula; Harm van Bakel; Mitchell Sullivan; Deena R. Altman; Daniel Caplivski (Case Reports in Infectious Diseases)
Pseudomonas aeruginosa is an opportunistic pathogen that rarely causes pneumonia in otherwise healthy patients. We describe a case of community-acquired P. aeruginosa pneumonia in a previously healthy individual who likely acquired the infection from a home humidifier.